2013
DOI: 10.7461/jcen.2013.15.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug-eluting Coronary Stents, Bare Coronary Stents and Self-expanding Stents in Angioplasty of Middle Cerebral Artery Stenoses

Abstract: ObjectiveThe purpose of this study is to investigate the results of treatment using stent-angioplasty for symptomatic middle cerebral arterial (MCA) stenosis and comparison of in-stent restenosis between drug-eluting stents (DES), bare metal coronary stents (BMS) and self-expanding stents (SES).Materials and MethodsFrom Jan. 2007 to June. 2012, 34 patients (mean age ± standard deviation: 62.9 ± 13.6 years) with MCA stenosis were treated. Inclusion criteria were acute infarction or transient ischemic attacks (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…To our knowledge, this is the first randomized, multicenter, prospective, drug-eluting stent trial for symptomatic intracranial stenosis and vertebral artery stenosis. Although it differed in its design and the type of stent used, this study showed similar results to some previous clinical trials (2,3,(5)(6)(7)(8)(9). In the current trial, a lower rate of ISR was shown with DES than with BMS in symptomatic intracranial arterial stenosis and vertebral artery stenosis.…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, this is the first randomized, multicenter, prospective, drug-eluting stent trial for symptomatic intracranial stenosis and vertebral artery stenosis. Although it differed in its design and the type of stent used, this study showed similar results to some previous clinical trials (2,3,(5)(6)(7)(8)(9). In the current trial, a lower rate of ISR was shown with DES than with BMS in symptomatic intracranial arterial stenosis and vertebral artery stenosis.…”
Section: Discussionsupporting
confidence: 86%
“…However, the investigators reported that there was no restenosis in the cases with drug-eluting stent (Lee et al 2013). The restenosis is associated with the angle of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The SSYLVIA study reported the restenosis rate of ≥50 % at 6 months was 32.4 % (The SSYLVIA Study Investigators 2004 ). However, the investigators reported that there was no restenosis in the cases with drug-eluting stent (Lee et al 2013 ). The restenosis is associated with the angle of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al compared DESs, bare-metal coronary stents (BMSs), and self-expanding stents (SESs) in angioplasty of MCA atherosclerotic stenosis. They reported a reduction of ISR with DESs compared with BMSs and SESs [19]. To combat the consequences of neointimal proliferation, DESs and balloon angioplasty alone have been used in a few cases to treat ISR [9].…”
Section: Discussionmentioning
confidence: 99%